A mixture of the probiotic strains Bifidobacterium longum CH57 and Lactobacillus brevis CH23 ameliorates colitis in mice by inhibiting macrophage activation and restoring the Th17/Treg balance. (December 2016) - Lim, Su-Min; Jeong, Jin-Ju; Jang, Se-Eun; Han, Myung Joo; Kim, Dong-Hyun
Highlights: A mixture of the probiotic strains Bifidobacterium longum CH57 and Lactobacillus brevis CH23 ameliorates colitis in mice by inhibiting macrophage activation and restoring the Th17/Treg balance. B. longum CH57 inhibited LPS-induced NF-κB activation in macrophages. L. brevis CH23 inhibited differentiation of splenocytes into Th17 cells. B. longum CH57 attenuated colitis in mice by inhibiting macrophage activation. L. brevis CH23 attenuated colitis in mice by restoring Th17/Treg disturbance. The probiotic mixture (CH23 and CH57) synergistically attenuated inflammation in vitro and in vivo. Abstract: In the present study, we isolated Bifidobacterium longum CH57, which suppresses macrophage activation, from human gut microbiota and Lactobacillus brevis CH23, which inhibit Th17 cell differentiation, from kimchi, and investigated anti-inflammatory effects of CH23, CH57, and their probiotic mixture (PM) in mice with TNBS-induced colitis. CH57 inhibited NF-κB activation in LPS-stimulated macrophages. Oral administration of CH57 in mice attenuated TNBS-induced colitis and TNF-α expression. CH23 inhibited IL-17 and RORγt expression in splenic T cells. Oral administration of CH23 in mice inhibited TNBS-induced colon shortening, myeloperoxidase activity, and Th17 cell differentiation and induced TNBS-suppressed Treg differentiation. PM increased TNBS-suppressed claudin, occludin, and ZO-1 expression and Treg differentiation, while CH57 inhibited Th17 cell differentiation and RORγt and IL-17 expression. PM inhibited TNBS-induced macrophage activation. Moreover, CH23 and CH57 synergistically inhibited macrophage activation and Th17 cell differentiation in vitro. The PM may synergistically ameliorate colitis by inhibiting macrophage activation and restoring Th17/Treg balance.